2017
DOI: 10.1038/ncomms14559
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of point defects in improving the specific capacitance of δ-MnO2 nanosheets

Abstract: 3D porous nanostructures built from 2D δ-MnO2 nanosheets are an environmentally friendly and industrially scalable class of supercapacitor electrode material. While both the electrochemistry and defects of this material have been studied, the role of defects in improving the energy storage density of these materials has not been addressed. In this work, δ-MnO2 nanosheet assemblies with 150 m2 g−1 specific surface area are prepared by exfoliation of crystalline KxMnO2 and subsequent reassembly. Equilibration at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
175
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(187 citation statements)
references
References 70 publications
11
175
0
1
Order By: Relevance
“…It is also more favorable for the electrochemical intercalation of electrolyte cations near the vacancies, which leads to enhanced rate capability in the defective MnO 2 for electrochemical intercalation/deintercalation. Following this pioneering study, more research works have been conducted to intentionally introduce cation vacancies into different transition metal oxides/carbides, such as MnO 2 , [ 89–93 ] TiO 2 , [ 94–96 ] Fe 2 O 3 , [ 77,78,97,98 ] ZnCo 2 O 4 , [ 99 ] ZnMn 2 O 4 , [ 76 ] and MXenes, [ 79,100–102 ] providing better and more fundamental understanding of the role of cation vacancies in boosting electrochemical performance ( Figure 2 ). Several density functional theory (DFT) calculations have also indicated that the presence of cation vacancies results in a decrease of energy barrier for ion diffusion, [ 95,103 ] and an increase of the materials' electronic conductivity, [ 80 ] thus benefits the charge storage process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also more favorable for the electrochemical intercalation of electrolyte cations near the vacancies, which leads to enhanced rate capability in the defective MnO 2 for electrochemical intercalation/deintercalation. Following this pioneering study, more research works have been conducted to intentionally introduce cation vacancies into different transition metal oxides/carbides, such as MnO 2 , [ 89–93 ] TiO 2 , [ 94–96 ] Fe 2 O 3 , [ 77,78,97,98 ] ZnCo 2 O 4 , [ 99 ] ZnMn 2 O 4 , [ 76 ] and MXenes, [ 79,100–102 ] providing better and more fundamental understanding of the role of cation vacancies in boosting electrochemical performance ( Figure 2 ). Several density functional theory (DFT) calculations have also indicated that the presence of cation vacancies results in a decrease of energy barrier for ion diffusion, [ 95,103 ] and an increase of the materials' electronic conductivity, [ 80 ] thus benefits the charge storage process.…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways for incorporating cation vacancies and tailoring its content in transition metal oxides/carbides through synthetic approaches, such as replacing the constituent cations or anions with aliovalent substitutes, [ 94–96,104,105 ] equilibration at solutions with different pH values, [ 89,90,99,106,107 ] selective removal of constituent cations, [ 101,102,108 ] thermal annealing in defects inducing atmospheres, [ 109,110 ] and plasma etching. [ 111 ] The characterization of cation vacancies, however, is usually challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization of rGO and h‐BN generates a stacking region where defects were created. The defects provided efficient nucleation sites for the growth of metal oxides by adsorbing the metal cations . Thus, the stoichiometry of the iron/nickel along with the rGO/h‐BN backbone was tuned by adjusting the applied bias of the bath solution.…”
Section: Introductionmentioning
confidence: 99%
“…e-g) Reproduced with permission [61]. b) Current-voltage plot of NiCo 2 O 4−x nanowires reduced with different hydrogen treatment times.…”
mentioning
confidence: 99%